Gene rfaH, which affects lipopolysaccharide core structure in Salmonella typhimurium, is required also for expression of F-factor functions. - Sanderson, K E (1981)
Mutations in gene rfaH of Salmonella typhimurium at 84 units on the linkage map make lipopolysaccharide of chemotypes Ra, Rb2, Rb3, and Rc (A. A. Lindberg and C. G. Hellerqvist, J. Gen. Microbiol, 116:25--32, 1980). F-factor expression in RfaH- strains was reduced in the following properties when compared with RfaH+ strains: transfer of Flac, number of phage f2 infective centers, lysis by and propagation of phages f2 and M13, proportion of cells with visible F-pili, and formation of mating aggregates with F- cells. Inhibition of multiplication of Br60, a female-specific phage, was not reduced in RfaH- Flac strains. Plasmid transfer from RfaH- strains was reduced for Inc groups FI, FII, and T, unaffected for Inc groups beta, I alpha, L, N, P, and W. and increased for Inc group M when compared with plasmid transfer from RfaH+ strains. Reduced F-factor function in RfaH- strains was not due to defective lipopolysaccharide since strains with mutations in other rfa genes were unaffected in plasmid transfer. Gene rfaH appears to be homologous with gene sfrB in Escherichia coli K-12, which maps at the same location, influences F-factor function, and affects synthesis of lipopolysaccharide. The gene product of sfrB has been proposed to be a transcription antiterminator.